Invited Editorial: How To Give A Good Talk - Zura Kakushadze (European Scientific Journal, ESJ, 2016)
I give my two cents on this subject based on what I have learned from others and my own experience. I avoid various abstract bullet points and convoluted, generic and cliché advice you can Google aplenty. Instead, I base my discussion on real-life examples accompanied by pictures, slides and stories. I discuss three basic parts to giving a good talk: i) picking a right subject; ii) good slides; and iii) delivery. I discuss tools for getting the job done to: i) convey to the audience why what you’re doing is important; ii) imprint a key message onto your audience; and iii) make your talk memorable.